Conceptual modeling of organic matter flows to assess agroecological transition. Final report WP 1.2 - Müller, Jean Pierre; Sanogo, Tingouro (2024)
The proposed intervention is to equip the Fatick DyTAEL (Dynamic for the agroecological transition) in Senegal with a simulation model to support the exploration of agro-ecological management options and enable the possible impact of these options to be estimated and discussed.